STUDY OF THE VARIABILITY OF SOME GALACTIC B[E] STARS - Miroshnichenko, A. S. (Одеські астрономічні публікації, 2017)
The photometric investigation of B[e]-stars MWC 84, MWC 342, MWC 623, and MWC 930, close to them on spectral characteristics, has been made. A brightness variability in the optical and near IR regions has been studied. Regular parts of the variability were detected for all the objects. The variability mechanisms are considered. Binarity evidences for MWC 84, MWC 342, and MWC 930 are presented. A comparison of objects spectral energy distribution (SED) with star models having circumstellar shells was carried out and main system parameters have been defined.